2020
DOI: 10.15252/embj.2020105537
|View full text |Cite
|
Sign up to set email alerts
|

Netrin‐1 and its receptor DCC modulate survival and death of dopamine neurons and Parkinson’s disease features

Abstract: The netrin-1/DCC ligand/receptor pair has key roles in central nervous system (CNS) development, mediating axonal, and neuronal navigation. Although expression of netrin-1 and DCC is maintained in the adult brain, little is known about their role in mature neurons. Notably, netrin-1 is highly expressed in the adult substantia nigra, leading us to investigate a role of the netrin-1/DCC pair in adult nigral neuron fate. Here, we show that silencing netrin-1 in the adult substantia nigra of mice induces DCC cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 34 publications
(40 reference statements)
4
51
0
Order By: Relevance
“…Recently, it has been indicated (Dominici et al, 2017;Varadarajan et al, 2017;Moreno-Bravo et al, 2019;Brignani et al, 2020) that the NTN1 protein can been located in axonal projections or concentrated in the pial surface and not in the area of the soma of the Ntn1-expressing neurons. The NTN1 presence in the mesodiencephalic dopaminergic neurons has been recently demonstrated in adult brains, and we have proved it during development (Dominici et al, 2017;Jasmin et al, 2020). Nevertheless, other authors have also described the NTN1 production by dopaminergic neurons of the developing SNc and VTA (Livesey and Hunt, 1997;Li et al, 2014;Brignani et al, 2020).…”
Section: Ntn1-dcc Mechanism Has a Complex Role In The Guidance Of Mhbsupporting
confidence: 73%
“…Recently, it has been indicated (Dominici et al, 2017;Varadarajan et al, 2017;Moreno-Bravo et al, 2019;Brignani et al, 2020) that the NTN1 protein can been located in axonal projections or concentrated in the pial surface and not in the area of the soma of the Ntn1-expressing neurons. The NTN1 presence in the mesodiencephalic dopaminergic neurons has been recently demonstrated in adult brains, and we have proved it during development (Dominici et al, 2017;Jasmin et al, 2020). Nevertheless, other authors have also described the NTN1 production by dopaminergic neurons of the developing SNc and VTA (Livesey and Hunt, 1997;Li et al, 2014;Brignani et al, 2020).…”
Section: Ntn1-dcc Mechanism Has a Complex Role In The Guidance Of Mhbsupporting
confidence: 73%
“…Although we know that Netrin-1/DCC is still expressed in adult SNpcs, the mechanism of DCC-mediated selective vulnerability has been elusive until recently. Using lossof-function rodent experiments, it was found that Netrin-1 deletion leads to α-synuclein aggregation and that unbound DCC could trigger the cell death pathways [128]. In this work, the authors also showed that overexpression of Netrin-1 could be neuroprotective in PD models.…”
Section: Snpc Da Neurons' Selective Vulnerability In Pdmentioning
confidence: 65%
“…This model has some limitations, as embryonic rodent neurons are used and the growth factor deprivation or neurotoxin poisoning do not replicate the real pathological situation in Parkinson’s disease. Nevertheless, it is a widely used cellular model to test the efficacy of growth factors and small molecules before testing them in animal models of Parkinson’s disease [ 39 , 40 ]. It has been demonstrated that the preferred cellular substrate for FTO is not the m 6 A but its further modification N 6 2′-O-dimethyladenosine (m 6 Am), which is exclusively found adjacent to the 7-methylguanine (m7G) cap in mRNA [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%